Intégrer les Tice à une approche cognitive de la grammaire du discours - Muriel Barbazan (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In the light of results from psycholinguistics and cognitive psychology concerning learning models and verbal production processes, this article follows up two objectives. Before exploring the potential development of grammatical activities in a digital learning environment, the first part will explore how we can conceive grammatical explanations aiming at an integration of current results from the discourse analysis and text linguistics. This first part aims at highlighting the usefulness of grammatical explanations when associated with prototypes of actual productions of utterances. At the same time textual functions of grammatical markers will be associated to complete the analysis of the textual structure. The second part of the article will investigate the possibilities to create didactic activities with ICT resources that could help FFL learners to internalize grammatical routines for an appropriate production and reception of discourses in real-life situations.